Stimulus Pulse-Based Distributed Control for the Locomotion of a UBot Modular Robot. (11th December 2013) - Zhu, Yanhe; Jin, Hongzhe; Fan, Jizhuang; Cui, Jinxiang; Yin, Jinchun; Liu, Pijun; Zhao, Jie
A distributed control algorithm based on a stimulus pulse signal is proposed in this paper for the locomotion of a Modular Self-reconfigurable Robot (MSRR). This approach can adapt effectively to the dynamic changes in the MSRR's topological configuration: the functional role of the configuration can be recognized through local topology detection, dynamic ID address allocation and local topology matching, such that the features of the entire configuration can be identified and thereby the corresponding stimulus signals can be chosen to control the whole system for coordinated locomotion. This approach has advantages over centralized control in terms of flexibility and robustness, and communication efficiency is not limited by the module number, which can realize coordinated locomotion control conveniently (especially for configurations made up of massive modules and characterized by a chain style or a quadruped style).